Utilisation of collagen extract from tilapia fish skin waste (Oreochromis niloticus) for tissue regeneration: Pemanfaatan ekstrak kolagen dari limbah kulit ikan nila tilapia (Oreochromis niloticus) untuk regenerasi jaringan - Putri, Nabilah Atikah; Ilhamsyah, Salsabyla Tamara Putri; Azzahra, Fatimah; Nusaly, Tiara Rezqi Megautama; Rieuwpassa, Irene Edith (Makassar Dental Journal, 2024)
Production and cultivation of tilapia fish (TF) (Oreochromis niloticus) in Indonesia is the second largest after China. However, TF waste is a potential pathogen. The waste of TF can be managed into valuable products, such as collagen extracts that can be used in dentistry in several dosage forms, such as sponges, hydrogels, membranes, and nano collagen fibres. There are various thera-peutic applications of collagen extracts from TF skin, especially in the field of dentistry, such as in the treatment of wounds heal-ing, dry socket healing, bone necrosis, grafting, flap surgery, and periodontal tissue regeneration. TF skin can be used as an ex-cellent and economical regenerative treatment to provide cost-effective treatment. However, larger-scale studies worldwide should be conducted before it is officially used widely.